Amylin peptide is increased in preterm neonates with feed intolerance. Issue 4 (5th February 2008) - Kairamkonda, V R; Deorukhkar, A; Bruce, C; Coombs, R; Fraser, R; Mayer, A-P T
Abstract : Background: Amylin, a 37-amino-acid peptide hormone, is a potent inhibitor of gastric emptying. It is co-secreted by the pancreatic β cells in response to enteral nutrient intake. Feed intolerance is common in preterm neonates and often presents as increased gastric residual volume (GRV). It is therefore hypothesised that serum amylin concentrations are raised in preterm neonates with poor gastric emptying, which may contribute to this observed feed intolerance. Objective: To determine serum amylin concentrations in feed-intolerant preterm neonates. Patients and methods: Feed-intolerant (nTOL) preterm neonates (GRV >50% of a previous 4 h feed volume on two consecutive occasions) were matched for gestation, birth weight and postnatal age with feed-tolerant (TOL) neonates. Blood samples were analysed for amylin concentration. Seventy neonates were studied with median (interquartile range) gestation of 29 weeks (28–33) and birth weight of 1.3 kg (1.0–1.8). Results: Serum amylin concentration and percentage GRV (median (interquartile range)) were significantly higher in the nTOL (47.9 pmol/l (21.4–79.8), 150% (100–350)) than the TOL (8.7 pmol/l (5.7–16), 5% (0–5)) group (p<0.001). In the nTOL group, a positive correlation was observed between serum amylin and GRV (r = 0.78, 95% CI 0.59 to 0.89, p<0.001), days to reach full enteral feeds (r = 0.40, 95% CI 0.08 to 0.68, p = 0.02), and days to discharge (r = 0.43, 95% CI 0.09 to 0.68, p = 0.01). Conclusions: Amylin may be responsible for delaying establishment of enteral nutrition in preterm neonates by virtue of its inhibitory effect on gastric emptying. Serum amylin concentrations in these neonates correlate with GRVs and time to reach full enteral feeds.